Patient Knowledge About Diabetes: Illness Symptoms, Complications and Preventive Personal Lifestyle Factors - Rakesh Kumar; Ramaiah Itumalla; Bilesha Perera; Mohamed Tharwat Elabbasy; Mahesh Singh (Health Psychology Research)
# Aims